Improving Local Roads and Creating Jobs through Rapid Response Projects : Lessons from Armenia Lifeline Roads Improvement Project - Ishihara, Satoshi (World Bank, Washington, DC, 2012)
In late 2008 the Republic of Armenia requested the Bank's assistance to mitigate the impact of the global financial crisis. This technical note describes how the Lifeline Road Improvement Project (LRIP) was prepared and implemented as a Rapid Response Project, prepared in only six weeks. This project saw over 150 km of roads improved and almost 12,000 person-months of employment generated during an eight month period between May to December 2009. The lessons learned may guide other projects with similar objectives.